Efeito do treinamento muscular inspiratório em pacientes portadores de doença do refluxo gastroesofágico - Holanda, Esther Studart da Fonseca (2013)
The gastroesophageal reflux disease (GERD) is a result of symptoms or lesions caused by acid reflux of gastric contents into the esophagus-peptic or supra-esophageal structures, through an antireflux barrier ineffective or insufficient defense mechanism. The lower esophageal sphincter (LES) is the main component of the antireflux barrier, comprised of an oesophageal component itself, and the other formed by the crural diaphragm. OBJECTIVE: The purpose of this randomized, controlled study was to evaluate the effect of inspiratory muscle training in patients with erosive esophagitis. METHOD: Twenty subjects with past history of GERD participated in this study. They were randomized to a control group – without load (WL group) or to an experimental group – with load (L group). All of them underwent clinical evaluation by endoscopy (EGD), manovacuometry, high-resolution manometry and pH monitoring before and after IMT with 50% of maximum inspiratory pressure (MIP), held three times a week, once a day, during eight weeks. Information regarding the subject’s age, sex, height, weight, medical history and current medical status were obtained by a questionnaire. A consent form was read and signed by the subjects before the initiation of the study. Student t tests and Wilcoxon were used to analyze the data. RESULTS: 10 subjects (3 males and 7 females - L group, aged from 43,2 ± 3,23 years) and 10 subjects (5 males and 5 females - WL group, aged 41,7±3,59 years). The experimental group tended to improve MIP more than the control group. A significant increase of MIP (76,9±6,6% to 105,6±8,6 % ρ=0.002; L group) versus (87,0±7,6% to 94,2±9,5% p=0,116; WL group), reduction of symptoms in relation to frequency of throat cleaning (2-4/week to < 1/week; ρ=0.016) and intensity of heartburn (2-4/week to <1 week; ρ=0.007). The L group increased the basal LES esophagus pressure (IMT 18,84±2,6 mmHg to 22,82±2,9 mmHg; ρ= 0.033) versus (25,26±3,9 mmHg to 25,04±3,3 mmHg p= 0,95) in those who did not receive a load training. No improvement in acid exposure of the distal after ITM. CONCLUSION: These data strongly support that's the IMT with linear load pressure increases MIP, baseline pressure respiratory average LES, possibly due to a significant improvement in mechanical efficiency of the crural diaphragm, reduces the frequency of heartburn and intensity of throat clearing, does not modify the acid exposure of the distal esophagus.